Structure and properties of Co‑Cr alloys for biocompatible medical products - P. E. Lushchik; I. V. Rafalski; V. T. Minchenya; L. P. Dolgi; A. V. Zablotski; A. Yu. Korolev (Литьë и металлургия)
The results of studies of Co‑Cr alloys for biocompatible medical products are presented. The article shows that alloys of CoCr‑W system are promising for the manufacture of coronary and vascular small‑sized stents with high radial rigidity of the structure. Ensuring the corrosion resistance of the material is one of the general requirements for implants of the Co‑Cr alloys. The main influence on the corrosion resistance, biocompatibility and mechanical properties of coronary and vascular implants subjected to increased cyclic loads is exerted by the state and structure of the surface of the Co‑Cr alloy. Effective ways to change the surface structure and improve the properties of Co‑Cr alloys are heat treatment processes, including those in vacuum, mechanical and electrochemical methods of surface treatment.